Proctolaelaps bickleyi (Acari: Mesostigmata: Melicharidae): First Record of Its Association with Cotton Boll Weevil - Silva, C. A.D.; Castilho, R. C. [UNESP]; Galvão Filho, A. L.A.; Zanuncio, J. C. (Springer Nature, 2020)
The objective was to register the occurrence of Proctolaelaps bickleyi (Bram) (Acari: Mesostigmata: Melicharidae) in association with adults of the Anthonomus grandis Boheman (Coleoptera: Curculionidae) and to describe aspects of its behavior. This is the first record of a mesostigmatid mite associated with the cotton boll weevil in the Americas. Beetles carrying the mites had lower mobility than usual. The stress caused by this mite attached to the A. grandis body can reduce mating and oviposition of this beetle.
Keywords: Abscised cotton; Anthonomus grandis Gossypium hirsutum; Predatory mite